Research on the Association of Consumption Structure With Industrial Structure and Economic Growth in Jinan City (Asian Business Research, 2022)
This paper empirically investigates the relationship between consumption structure, industrial structure andeconomic growth in Jinan City using vector autoregressive (VAR) model using 30 years of data from 1990-2020in Jinan City. The results show that there is a two-way causal relationship between industrial structure andeconomic growth, and a two-way causal relationship between consumption structure and economic growth inJinan City. Consumption structure can promote the optimization of industrial structure and further promoteeconomic growth, while industrial structure does not play a proper role in promoting the regulation ofconsumption structure.